Making Investment Decisions on Shares of Bank Syarī’ah Indonesia Company with Price to Book Value (PBV) Approach - M. Syukri Ismail; Febrianto, Achmad; Ira Febriliana Dewi Riza; Bannaga Taha Al-Zubair Hussen (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This research was conducted to determine the fundamental condition of Bank Syarī’ah Indonesia company in making investment decisions in Bank Syarī’ah Indonesia company (issuer code: BRIS). This research uses a quantitative method with a Price Book Value (Pbv) approach. The data used in this study is secondary data obtained from the Indopremier Securities, Stockbit Securities, and RTI Business applications, which originate from the annual reports of Bank Syarī’ah Indonesia companies for the 2018-2022 period, to be precise in the 3rd Quarter of 2022. The fundamental analysis forms by looking at the profile and the company's prospects, then analyzing the company's performance through the company's financial statements from 2018 to 2022. Fundamental analysis is also carried out by comparing the performance of Bank Syarī’ah Indonesia company with competitors in shares of the Syarī’ah financial sector, namely BTPN Syarī’ah (issuer code: BTPS) and Bank Aladin Syarī’ah (issuer code: BANK). Activities are carried out by calculating the intrinsic value or fair price of Bank Syarī’ah Indonesia shares using the PBV approach and completing investment decisions. The study found that Bank Syarī’ah Indonesia's corporate performance is good. The company's fundamental condition is also good, and its stock valuation is undervalued; based on these two analyses, Bank Syarī’ah Indonesia's shares are worth buying.